Manias, panics, and crashes : a history of financial crises - Kindleberger, Charles P. (New York : Basic Books, 1978)
This book is on financial crisis which is associated with peaks of business cycles, the rhythm of economic expansion and contraction
Includes bibliographical references and index.
oo 23/08/2018
Loans
Keywords: Business cycles; Depressions; Financial crises